KONSEP ASAS PEMBENTUKAN INDIKATOR BANDAR SEJAHTERA MENURUT PERSPEKTIF ISLAM(BASIC CONCEPT OF THE WELL-BEING CITY FROM ISLAMIC PERSPECTIVE) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
City is the central development of the human civilization. The emergence of Islam as a greatest religion and most glorious began from the city. The aims of the study are to identify the concepts, principles and characteristics of wellbeing Islamic city and to establish indicators based on Islamic scholars opinion. It is also to measure the level of wellbeing city based on the indicators produced and to identify the implications of planning policy and urban community development. Result shows that, economic, faith and physical scored highest for developing cultural-economic indicators among the population endowment scored min 4.91. Faith-resident reading al-Quran as a daily practice indicator scored 4.90 and physical indicators of the existence of a clean environment scored min 4.89. Overall, the study found that the wellbeing of a city influenced by spiritual compared with physical factors.
Keywords: Indicator; City; Development; Well Being; Urban Planning